Advance care planning in patients with incurable cancer: study protocol for a randomised controlled trial. Issue 12 (1st December 2016) - Johnson, Stephanie; Clayton, Josephine; Butow, Phyllis N; Silvester, William; Detering, Karen; Hall, Jane; Kiely, Belinda E; Cebon, Jonathon; Clarke, Stephen; Bell, Melanie L; Stockler, Martin; Beale, Phillip; et al.
Abstract : Introduction: There is limited evidence documenting the effectiveness of Advance Care Planning (ACP) in cancer care. The present randomised trial is designed to evaluate whether the administration of formal ACP improves compliance with patients' end-of-life (EOL) wishes and patient and family satisfaction with care. Methods and analysis: A randomised control trial in eight oncology centres across New South Wales and Victoria, Australia, is designed to assess the efficacy of a formal ACP intervention for patients with cancer. Patients with incurable cancer and an expected survival of 3–12 months, plus a nominated family member or friend will be randomised to receive either standard care or standard care plus a formal ACP intervention. The project sample size is 210 patient–family/friend dyads. The primary outcome measure is family/friend-reported: (1) discussion with the patient about their EOL wishes and (2) perception that the patient's EOL wishes were met. Secondary outcome measures include: documentation of and compliance with patient preferences for medical intervention at the EOL; the family/friend's perception of the quality of the patient's EOL care; the impact of death on surviving family; patient–family and patient–healthcare provider communication about EOL care; patient and family/friend satisfaction with care; quality of life of patient and family/friend subsequent to trial entry, the patient's strength of preferences for quality of life and length of life; the costs of care subsequent to trial entry and place of death. Ethics and dissemination: Ethical approval was received from the Sydney Local Health District (RPA Zone) Human Research Ethical Committee, Australia (Protocol number X13-0064). Study results will be submitted for publication in peer-reviewed journals and presented at national and international conferences. Trial registration number: Pre-results; ACTRN12613001288718 .